The case of cross-border pure online program : crossing boundaries, engaging minds - Lim , Tina Swee Kim; Zoraini Wati Abas; Kaur, Abtar (2010)
According to UNESCO (2002), new forms of distance learning based on new information and communication technologies are emerging and this has led to a significant trend towards intensifying globalization. Such forms of learning are a result of new learning needs and new patterns of information access and application. In the case of learning that is mediated solely through the use of such technologies, the content and activities need to be so designed that they are able to adequately compensate face-to-face meetings that have always been considered crucial in blended modes of open and distance learning. This paper seeks to describe and examine learner engagement in a pure online open and distance learning master’s program that was offered to students from 12 countries by Open University Malaysia based on feedback obtained via an online survey and personal e-mail. (Authors' abstract)